2015
DOI: 10.1111/eci.12476
|View full text |Cite
|
Sign up to set email alerts
|

Sepsis biomarkers in neutropaenic systemic inflammatory response syndrome patients on standard care wards

Abstract: In neutropaenic SIRS patients, none of the evaluated biomarkers was able to adequately identify infection. LBP and PCT presented a good performance in identifying bacteraemia. Therefore, these markers could be used for screening purposes to increase the pretest probability of blood culture analysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 40 publications
(63 reference statements)
1
12
0
Order By: Relevance
“…Between July 2011 and September 2012, patients with clinically suspected sepsis were evaluated on 14 medical and 13 surgical standard care wards of Vienna General Hospital (latitude 48°N), Austria. As described elsewhere52535455, patients for whom the treating physician had requested a blood culture analysis were screened for fulfilment of two or more SIRS criteria, as defined by the ACCP/SCCM conference56. Iatrogenic neutropenia related to chemotherapy was not recognized as a valid SIRS criterion.…”
Section: Methodsmentioning
confidence: 99%
“…Between July 2011 and September 2012, patients with clinically suspected sepsis were evaluated on 14 medical and 13 surgical standard care wards of Vienna General Hospital (latitude 48°N), Austria. As described elsewhere52535455, patients for whom the treating physician had requested a blood culture analysis were screened for fulfilment of two or more SIRS criteria, as defined by the ACCP/SCCM conference56. Iatrogenic neutropenia related to chemotherapy was not recognized as a valid SIRS criterion.…”
Section: Methodsmentioning
confidence: 99%
“…122 However, in neutropenic patients with sepsis, neither PCT nor CRP differed significantly between patients with and without an infection, thus they seem to offer little help in early differentiation between bacterial infection and inflammation in this population. 123 …”
Section: Diagnosismentioning
confidence: 99%
“…The role of PCT in detecting sepsis in immunocompromised patients, however, remains controversial as studies have shown conflicting results. [32][33][34][35] On the other hand, PCT has demonstrated an acceptable accuracy for the diagnosis of bacterial infections in septic patients with liver cirrhosis compared to patients with normal liver function. [36] These results contrast with those of Tang et al [37] who described a low diagnostic performance of PCT in differentiating sepsis from non-infectious SIRS in critically ill adults.…”
Section: Pct As a Diagnostic Toolmentioning
confidence: 99%